Amoxicillin Administration Regimen and Resistance Mechanisms of Staphylococcus aureus Established in Tissue Cage Infection Model - Yao, Qian; Gao, Linglin; Xu, Teng; Chen, Yun; Yang, Xin; Han, Mengmeng; He, Xiaotao; Li, Chengheng; Zhou, Ruigang; Yang, Yuhui (Frontiers in Microbiology, 2019)
Staphylococcus aureus is a zoonotic pathogen that causes various life-threatening diseases. Amoxicillin has strong antimicrobial activity against S. aureus, but its mechanisms of resistance development are unclear. In this study, we used a rabbit tissue cage infection model to evaluate the relationship between pharmacokinetic/pharmacodynamic (PK/PD) parameters and selective enrichment of resistant strains of S. aureus, and to elucidate the evolution of its resistance to amoxicillin. S. aureus was injected into the tissue cages at 1010 colony forming units (CFU)/mL. We injected different intramuscular concentrations of amoxicillin at doses of 5, 10, 20, and 30 mg/kg body weight once a day for 5 days and 5, 10, 20, and 30 mg/kg body weight twice a day for 2.5 days. Differences in gene expression between two differentially resistant strains and a sensitive strain were evaluated using Illumina sequencing followed by COG and KEGG analysis. RT-qPCR was carried out to validate the difference in protein translation levels. Our results demonstrated that the emergence of resistant bacteria was dose-dependent within a given time interval. In the same dosage group, the appearance of resistant bacteria increased as time progressed. The resistant bacteria showed cumulative growth, and the level of resistance rose over time. The resistant bacteria were completely inhibited when the cumulative percentage of time over a 24-h period that the drug concentration exceeded the mutant prevention concentration (MPC) (%T > MPC) was ≥ 52%. We also found that the expression of mecA and femX in S. aureus played a leading role in the development of resistance to amoxicillin. In conclusion, these data provide meaningful guidance for optimizing amoxicillin regimens to treat infections caused by S. aureus.